Citrate: a key signalling molecule and therapeutic target for bone remodeling disorder - Qichang Liu; Yuchuan Xue; Junzhe Guo; Lin Tao; Yue Zhu (Frontiers in Endocrinology)
Bone remodeling is a continuous cyclic process that maintains and regulates bone structure and strength. The disturbance of bone remodeling leads to a series of bone metabolic diseases. Recent studies have shown that citrate, an intermediate metabolite of the tricarboxylic acid (TCA) cycle, plays an important role in bone remodeling. But the exact mechanism is still unclear. In this study, we focused on the systemic regulatory mechanism of citrate on bone remodeling, and found that citrate is involved in bone remodeling in multiple ways. The participation of citrate in oxidative phosphorylation (OXPHOS) facilitates the generation of ATP, thereby providing substantial energy for bone formation and resorption. Osteoclast-mediated bone resorption releases citrate from bone mineral salts, which is subsequently released as an energy source to activate the osteogenic differentiation of stem cells. Finally, the differentiated osteoblasts secrete into the bone matrix and participate in bone mineral salts formation. As a substrate of histone acetylation, citrate regulates the expression of genes related to bone formation and bone reabsorption. Citrate is also a key intermediate in the metabolism and synthesis of glucose, fatty acids and amino acids, which are three major nutrients in the organism. Citrate can also be used as a biomarker to monitor bone mass transformation and plays an important role in the diagnosis and therapeutic evaluation of bone remodeling disorders. Citrate imbalance due to citrate transporter could result in the supression of osteoblast/OC function through histone acetylation, thereby contributing to disorders in bone remodeling. Therefore, designing drugs targeting citrate-related proteins to regulate bone citrate content provides a new direction for the drug treatment of diseases related to bone remodeling disorders.